Obsidian in the prehistoric Aegean: Trade and uses - Tsampiri, Mailinta (Bulletin of the Geological Society of Greece, 2018)
This paper studies the prehistoric use of obsidian quarries in the Aegean. Obsidian sources in the eastern Mediterranean have been traced on certain islands of the Aegean: Melos, Antiparos and Giali. Due to its hardness, this material was already being used by the end of the Upper Palaeolithic to produce blades with sharp edges to serve as knives, scrapers and razors, arrowheads and spears, axes, saws and mattocks. This naturally occurring glass was also used for ornamental purposes. During the Late and the Final Neolithic Period (ca. 5300-3200 B.C.), when the systematic habitation of the Cyclades developed, the transportation of obsidian was incorporated in the gradually developing trade networks of the Aegean. The material was much in demand in the early Bronze Age. During the later Bronze Age its use declined and by the classical period it seems to have been replaced by metal. Around 1100 B.C. the use of obsidian was discontinued because of the increasing popularity of metals. During the Roman period obsidian, was used in the manufacture of mosaics and decorative objects, such as mirrors